Digitalization of Gearing Ratio Program to Mitigate Financial Risk of Indonesian Credit Guarantee Industry - Muljono, Hari Tohar; Ratnawati, Tri; Sihab, M. Ridwan (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Digitalization in the credit guarantee industry in Indonesia is a strategic step to strengthen MSMEs’ access to financing. By utilizing digital technology, credit guarantee companies can overcome the limitations of MSMEs in obtaining capital through the provision of guarantees to banks. This research aims to understand how the implementation of digitalization in the gearing ratio program can improve credit guarantee efficiency and optimize financial risk mitigation at PT Jamkrida Jatim. Using a qualitative approach with a phenomenological method, data was collected through in-depth interviews, focus group discussions (FGDs), and document analysis. The results show that digitizing the gearing ratio program strengthens accountability and transparency, and enables real-time risk monitoring. With a digitized decision evaluation process (“Go,” “No Go,” and “Cut Loss”), PT Jamkrida Jatim can mitigate financial risks more precisely and efficiently. Digitalization also enables better internal collaboration and rapid response to market conditions. Overall, this research underscores the important role of digitalization in creating an inclusive, sustainable MSME financing ecosystem and supporting national economic growth through better risk mitigation.